A metal-free synthesis of oxindoles by a radical addition-cyclization onto N-arylacrylamides with xanthates. Issue 12 (25th March 2015) - Wang, Shucheng; Huang, Xuhu; Li, Bowen; Ge, Zemei; Wang, Xin; Li, Runtao
Abstract: A convenient, high yielding synthesis of oxindoles by metal-free di-functionalization of alkenes with xanthates has been developed. This transformation involves a radical addition/cyclization process. Various arylalkylation products including alkyl ester-, benzyl-, cyano-, ketone-, amine-, and amide-substituted oxindoles were prepared in good to excellent yields. Graphical abstract: